Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Kemampuan Cerita Siswa SD Inpres Minasaupa 1 - Yuliani; Andi Sukri Syamsuri; Haslinda (Journal of Cultural Relativism (JCR), 2024)
This research aims to improve the storytelling abilities of fourth grade students at SD Inpres Minasa Upa 1 by implementing the Project Based Learning learning model. This research approach is CAR or Classroom Action Research which is carried out in two cycles, namely cycles I and II. This research can be categorized into four, namely: (1) participatory action research, critical action research, institutional action research, and classroom action research. Data collection techniques in this research used observation and tests. From cycle I to cycle II, there was an increase of 13% from 13 students who completed 9 students and 4 students who did not complete. Because they come from broken homes and have uneducated families so they don't pay enough attention to studying, apart from that they lack motivation and desire to achieve. The results of this research also show a significant increase in the learning process and learning outcomes, a conducive classroom atmosphere and student interest in participating in learning. The results of this research show that there is an increase in student achievement in each cycle, at each meeting in cycle I, meeting I has an average score of 60.76 with a completion percentage of 30.76% and at meeting II the average score is 68.84 with a completion percentage of 46. .15%. cycle II, meeting I average value was 74.15 with a percentage of 61.53% and meeting II average value was 80.76 with a percentage of 69.53%.